2021
DOI: 10.1039/d1ta07073h
|View full text |Cite
|
Sign up to set email alerts
|

9.63% efficient flexible Cu2ZnSn(S,Se)4 solar cells fabricated via scalable doctor-blading under ambient conditions

Abstract: The application of doctor-blading for flexible solar cells is considerably attractive due to its potential upscaling feasibility via roll-to-roll process. Herein, we report the fabrication of efficient flexible Cu2ZnSn(S,Se)4 (CZTSSe)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
1
15
1
Order By: Relevance
“…Lin et al (from Sun Yat‐Sen University) reported the fabrication of efficient Mo foil‐based FCSs by doctor blading under atmospheric environmental conditions. [ 44 ] They found that a large number of cracks formed in the precursor film when the sodium‐containing ink was blade coated, resulting in uneven growth of large grains along the cracks. Therefore, an alternative coating process for sodium‐free and sodium‐containing inks was developed to continuously suppress the cracks.…”
Section: Flexible Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al (from Sun Yat‐Sen University) reported the fabrication of efficient Mo foil‐based FCSs by doctor blading under atmospheric environmental conditions. [ 44 ] They found that a large number of cracks formed in the precursor film when the sodium‐containing ink was blade coated, resulting in uneven growth of large grains along the cracks. Therefore, an alternative coating process for sodium‐free and sodium‐containing inks was developed to continuously suppress the cracks.…”
Section: Flexible Substratesmentioning
confidence: 99%
“…In recent years, the power conversion efficiency (PCE) of FCSs has developed rapidly and has exceeded 11%, as shown in Figure 1b. In the research, flexible glass, [ 39 ] polyimide, [ 40,41 ] and metal foils [ 42–69 ] are used as flexible substrates. The FCSs reported in recent years are mostly fabricated on Mo foils, stainless steel (SS) foils, and Ti foils.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the dominant impurities in Mo foil are S and Cu, both of which are benign to CZTSSe, no additional impurity diffusion barrier is required. Mo foil is also compatible with various precursor deposition processes, such as sputtering, spin-coating, and doctor-blading, achieving 11.2% 67 , 10.2% 68 , and 9.6% 69 efficiencies respectively with the incorporation of sodium. The 11.2% efficiency is achieved by DGIST.…”
Section: Flexible Thin-film Kesterite Solar Cellsmentioning
confidence: 99%
“…[1][2][3][4][5] Compared with crystal silicon solar cells, thin-lm solar cells have greater scope for cost reduction and can be embedded in building-attached photovoltaic (BAPV) and building-integrated photovoltaic (BIPV) applications. [6][7][8] Chalcogenide CdTe and CIGS solar cells have demonstrated efficiencies of over 20% and long-term stability and have been commercially available for decades. 9,10 From a sustainability perspective, CdTe and CIGS solar cells can hardly dominate the PV market, mainly due to the scarcity of Te, In, and Ga. [11][12][13][14] High abundance, low-priced, and eco-friendly semiconductors are thus needed for high-performance thin-lm solar cells.…”
Section: Introductionmentioning
confidence: 99%